2-(5-Iodo-2-oxoindolin-3-ylidene)hydrazinecarbothioamide including an unknown solvate - Viviane Conceição Duarte de Bittencourt (Acta Crystallographica Section E, 2014)
The molecule of the title compound, C9H7IN4OS, is almost planar (r.m.s. deviation = 0.0373 Å). In the molecule, N—H...N and N—H...O hydrogen bonds generate, respectively, S(5) and S(6) ring motifs. In the crystal, molecules are linked via N—H...O hydrogen bonds, forming chains propagating along [010]. These chains are linked via S...I contacts [3.4915 (16) Å], forming sheets lying parallel to (100). A region of disordered electron density, probably a disordered tetrahydrofuran solvent molecule, was treated using the SQUEEZE routine in PLATON [Spek (2009). Acta Cryst. D65, 148–155]. The formula mass and unit-cell characteristics were not taken into account during refinement.